Photocurrents in \(\text{GaAs}\) Quantum Wires Including Excitonic Effects - Duc, Huynh Thanh; Ngo, Cong (Communications in Physics, 2021)
Photocurrent induced by ultrashort laser pulses in [100]-oriented GaAs quantum wires with square cross section is investigated using the multiband semiconductor Bloch equations with the inclusion of electron-hole interaction. Influences of excitonic effects and quantum confinement effects on the photocurrent are evaluated and discussed